Implementasi Alokasi Dana Desa Pada Peningkatan Pemberdayaan Masyarakat Di Kelurahan Kapas Kabupaten Nganjuk - Kumba Digdowiseiso; Rinaldi Nur Satria Ananda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to explain the management of village funds and their implementation in village development, which in this case is to understand the use of APBDes in Kapas Village which is related to infrastructure development, empowerment and community development. This research is presented descriptively qualitatively, and is located in Kapas Village, Sukomoro District, Nganjuk Regency. The conclusion of this research states that Kelurahan Kapas has been good at implementing its village fund allocation. This can be seen in the APBDes 2022 data which is neatly arranged in the APBDes implementation report where it lies in the priority use of village funds which is quite appropriate even though the realization has not been maximized in the field of empowerment. The Village Law states that the use of the village fund budget must be aligned between empowerment and infrastructure development so that development can go hand in hand. In addition, the use of village funds in terms of community development is still not maximized in realization. As a result, budget absorption is not maximized for the benefit of the community in Kapas Village. Keywords: Empowerment, Implementation, Allocation, Village Fund.